1999
DOI: 10.1046/j.1464-410x.1999.00022.x
|View full text |Cite
|
Sign up to set email alerts
|

Urinary incontinence in Northern Ireland: a prevalence study

Abstract: Objective To determine the prevalence of urinary inconto 12.3% (85) of the total study population. Age (x2= 20.34; P<0.001) and parity (Mann-Whitney U-test, tinence in a Northern Ireland community drawn from four neighbouring geographical areas and to assess P< 0.001) were associated with urinary incontinence, with a higher proportion of women aged 45-54 years factors predisposing to the development of urinary incontinence.having urinary incontinence. The menopause and postnatal pelvic floor exercises were not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0
2

Year Published

2000
2000
2009
2009

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 10 publications
3
24
0
2
Order By: Relevance
“…To keep the collective as homogenous as possible, we only included postmenopausal women. It has been proposed that the prevalence of urinary incontinence is higher in the perimenopause, but this could not be veri¢ed [Dolan et al, 1999]. However, it is known that ageing may a¡ect the lower urinary tract in several ways, creating a predisposition to incontinence [Resnick and Yalla, 1985].…”
Section: Discussionmentioning
confidence: 99%
“…To keep the collective as homogenous as possible, we only included postmenopausal women. It has been proposed that the prevalence of urinary incontinence is higher in the perimenopause, but this could not be veri¢ed [Dolan et al, 1999]. However, it is known that ageing may a¡ect the lower urinary tract in several ways, creating a predisposition to incontinence [Resnick and Yalla, 1985].…”
Section: Discussionmentioning
confidence: 99%
“…Overall, about half of those with moderate or severe urinary incontinence and over half of those with daily episodes of urinary incontinence (Table 6) do not seek help. Previous studies have reported help-seeking as being around 8.8, 19 20, 22 12.8, 20 and 25% 1 of incontinent women. This demonstrates that although the present sample were accessing primary care services they were no more likely to consult about their symptoms than a general population sample.…”
Section: Treatment Pathwaysmentioning
confidence: 90%
“…interviewed primigravidae at 34-40 weeks. At interview, women were invited to participate and they self-completed a structured urinary incontinence questionnaire, adapted from a previous study [9]. On the urinary incontinence questionnaire, women were asked if they had experienced any urinary incontinence within the last 3 months and indicated the frequency and circumstances of this symptom.…”
Section: Methodsmentioning
confidence: 99%
“…At 3-5 days postpartum, women were asked to self-complete the structured urinary incontinence questionnaire in which they were asked if they had experienced any urinary incontinence since delivery [9]. Intrapartum details were obtained from obstetric notes and delivery suite computerised records.…”
Section: Methodsmentioning
confidence: 99%